Acid pretreatment of WC-Co for surface roughening and cobalt removal prior to CVD diamond coating - Norafifah, H.; Noordin, M.; Izman, S.; Kurniawan, Denni (2013)
Chemical vapor deposition (CVD) diamond coatings are being developed to be applied on carbide cutting tools to enhance wear resistance and increase tool life. As a prerequisite, for ensuring adhesion of CVD diamond on tungsten carbide substrate, it is necessary to prepare high surface roughness and to remove the cobalt on tungsten carbide surface during the pretreatment. In this study, a two step acid pretreatment was examined for those purposes. Etching using modified Murakami's reagent was initially performed to roughen the surface. Subsequently, the carbide was immersed in nitric acid to remove cobalt. Concentration of the acid solutions and reaction time were varied. Results showed that the initial step by modified Murakami's reagent etching resulted in a surface roughness of Ry = 6.95 µm, which is a 15% increase from the average initial surface roughness. The second step by nitric acid immersion on modified Murakami's reagent etched carbide samples resulted in carbide surfaces with zero cobalt content, confirming the effectiveness of the pretreatment. © (2013) Trans Tech Publications, Switzerland.